Ethnic representation in interventional clinical trials run in India - Jaishree Mendiratta; Mounika Pillamarapu; Indraneel Chakraborty; Ravi Vaswani; Mudit Kapoor; Sreekar Vadlamani; Gayatri Saberwal (Elsevier, 2023)
Summary: Globally, the need to enhance the diversity of trial participants is receiving increasingly urgent attention. We wanted to know whether trials run in India had adequately sampled the country's enormous ethnic diversity. We accessed the Clinical Trials Registry-India website to determine whether each interventional drug or biologic Phase 2 or 3 study, registered in a recent five-year period had run in each of six geographic zones. As regards Phase 3 trials conducted only in India, 61.4% ran in a single zone and just 6.8% were conducted in all six zones. Multinational Phase 3 trials had a better distribution since 3.6% had run in just one zone and 7.1% in all six. India's diverse ethnic groups are underrepresented in the majority of trials covered in this study. A trial that is conducted on non-representative groups and later discovered to be harmful or ineffective in parts of the population, is unethical. We propose various remedial steps.